Вплив аналогів /миметиків глюкагоноподібного пептиду 1 на варіативність глікемії та його значення у зниженні ризику кардіоваскулярних ускладнень цукрового діабету - Бабенко, А. Ю.; Лихоносов, М. П.; Лихоносова, А. П. (Clinical Endocrinology and Endocrine Surgery, 2014)
Scientific debate about the optimal control of types 1 and 2 diabetes mellitus are continued. What blood glucose levels considered acceptable, what should be the measure of glycated hemoglobin, which parameters depend on these parameters – these are the questions on which there is no definite answer. Moreover not only attention has been paid to control fasting and postprandial but also to introduce new concepts such as the variability of blood glucose, the coefficient of variation. Increasingly being used in everyday practice a continuous glucose monitoring, blood glucose self-control. Such attention to indicators of blood glucose levels during the day is induced due to the fact that poorly controlled blood glucose fluctuations increase the risk of cardiovascular complications of diabetes. In connection with this use of the new group of preparations – agonists of GLP-1 – opens new possibilities in the treatment of diabetes and prevention of its complications due to reduction of variability of glycemia.